Politics and development in the North American Arctic : examining the regional consequences of climate change - Czamy, Roman S.; Tomala, Magdalena; Wronska, Iwona (Emerald Publishing Limited, 2021)
The monograph analyzes international relations in the Arctic from two perspectives: cooperation and competition. The following question was asked: does rivalry outweigh cooperation in the Arctic or is it the other way round; do the entities manage to gain the benefits of cooperation? The authors pose the hypothesis that States and the Arctic actors should cooperate with each other in the light of the prisoner's dilemma of obtaining tangible benefits, but the more probable, and definitely more possible variant of absence of such a cooperation or breaking the cooperation is rivalry, which in the short-term gives an advantage over other players, but in the long-term causes losses.